Investigation on Alumina Passivation for Improved IGZO TFT Performance. (25th April 2016) - Mudgal, Tarun; Edwards, Nicholas; Ganesh, Prashant; Bharadwaj, Anish; Manley, Robert G.; Hirschman, Karl D
Abstract : A study of the influence of back-channel alumina passivation on the operation of bottom-gate IGZO TFTs is presented. TFTs without any passivation material deposited typically exhibit best-case initial results. Regardless a passivation layer is required for device stability and process integration. The impact of passivation using alumina deposited via electron beam evaporation and atomic layer deposition (ALD) has been investigated. A decrease in subthreshold slope and channel mobility on certain treatment combinations is attributed to an inferior IGZO/alumina back-channel interface. A two-step passivation process has been developed which offers back-channel protection during device fabrication, and remains compatible with an oxidizing ambient anneal. Modifications in the passivation and annealing procedures and process integration details have resulted in a marked improvement in the performance of alumina passivated devices, with demonstrated resistance to aging.